2003
DOI: 10.1007/s00775-002-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism for platination of thione-containing nucleotides and oligonucleotides: evaluation of the salt dependence

Abstract: Reactions of cis-[PtCl(NH(3))(CyNH(2))(OH(2))](+) (Cy=cyclohexyl) with thione-containing single-stranded oligonucleotides d(T(8)XT(8)) and d(XT(16)) (X=(s6)I or (s4)U) and the mononucleotides 4-thiouridine ((s4)UMP) and 6-mercaptoinosine ((s6)IMP) have been studied in aqueous solution at pH 4.1. The reaction kinetics was followed using HPLC methodology as a function of ionic strength in the interval 5.0 mM Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(73 reference statements)
2
4
0
Order By: Relevance
“…These values thus well reflect the more pronounced salt dependence observed Table 1 Observed pseudo-first-order rate constants for platination of d(T 6 GT 6 ), d(T 12 GT 12 ), and d(T 24 GT 24 ) as a function of monovalent cations; in the absence of polycations, and in the presence of 10 lM spd 3+ and 10 lM spn 4+a,b,c for reactions with the two shorter oligomers. The magnitude of the here obtained values agree well with previous determinations based on kinetic studies monitoring platinum binding to dðT s6 8 IT 8 Þ and dðT s4 8 UT 8 Þ with nW = 0.80 ± 0.02 and 0.74 ± 0.05, respectively [45]. Further, the present nW -values are significantly higher than those recently obtained for folded DNA hairpin structures of an overall length of 13 bases for which nW was determined to ca.…”
Section: Influence Of Na + Concentration On the Kinetics For Oligonucsupporting
confidence: 91%
See 3 more Smart Citations
“…These values thus well reflect the more pronounced salt dependence observed Table 1 Observed pseudo-first-order rate constants for platination of d(T 6 GT 6 ), d(T 12 GT 12 ), and d(T 24 GT 24 ) as a function of monovalent cations; in the absence of polycations, and in the presence of 10 lM spd 3+ and 10 lM spn 4+a,b,c for reactions with the two shorter oligomers. The magnitude of the here obtained values agree well with previous determinations based on kinetic studies monitoring platinum binding to dðT s6 8 IT 8 Þ and dðT s4 8 UT 8 Þ with nW = 0.80 ± 0.02 and 0.74 ± 0.05, respectively [45]. Further, the present nW -values are significantly higher than those recently obtained for folded DNA hairpin structures of an overall length of 13 bases for which nW was determined to ca.…”
Section: Influence Of Na + Concentration On the Kinetics For Oligonucsupporting
confidence: 91%
“…The observed pseudo-first-order rate constants, k obs , are listed in Table 1, and shown as a function of monovalent cation concentration in Fig. 2a-c. As previously shown for similar systems, the platination rate decreased with increasing cation concentration [32,43,[45][46][47]61]. The salt dependence differs slightly between the three oligonucleotides studied.…”
Section: Influence Of Na + Concentration On the Kinetics For Oligonucsupporting
confidence: 65%
See 2 more Smart Citations
“…25 Previous studies have shown that the Cl Ϫ ligand trans to the coordinated cyclohexylaminemoiety is the most labile one, 37 however, the other Cl Ϫ ligand is also labile giving rise to a mixture of aqua-complexes with similar reactivity in the solution. 32…”
Section: Preparation Of Platinum Compoundsmentioning
confidence: 99%